Pelatihan Pemanfaatan Barang Bekas sebagai Bahan Pembuatan Reusable Bag untuk Melatih Siswa Madrasah Ibtidaiyah dalam Melakukan Diet Plastik - Ulya, Ekadina Dzawil (Universitas Muhammadiyah Semarang, 2017)
Environmental issues have now become a global issue, one of which is the use of plastic in the bag. The use of plastics in modern life looks very rapidly, causing the level of human dependence on the higher the plastic. This resulted in the amount of plastic waste growing more and more. Various efforts to reduce the use of plastics have been done, namely by using methods 3R or Recycle, Reuse, and Reduce. But the fact is that people's knowledge about efforts to reduce the use of plastic is still lacking. Efforts to understand the young generation of plastic dangers is one solution to reduce the use of plastics. Therefore it is necessary to do reusable bag manufacturing as one solution to the problem. Researchers do devotion in MI Mu'awanah Muslimin Muslimat to train students to make reusable bag. Data were collected using observation, lecture, question and answer, and demosntration. Theaverage value of creativity of product that produced by class VI is around 83 while class VI is around 89. The average value of neatness and arranging equipment after doing activity on the same grade student equal to 80, while the students of class VI successively 83 and 80. From data obtained by good student enthusiasts in following the service program and produce products that can be used to reduce the use of plastics. Keywords: Environment, Plastic, Reusable Bag